A GAME BASED APPROACH FOR LEARNING SINDHI ALPHABETS: A COMPARATIVE STUDY - Saifullah Lail; Suhni Abbasi; Saima Shaikh; Kavita Tabbassum; Mukhtiar Memon; Muhammad Asad Ali (Spectrum of Engineering Sciences, 2025)
Game-Based Learning (GBL) is a subset of serious games that utilizes digital games or software applications with educational purposes, aiming to achieve specific learning goals through interactive gameplay. In the Sindh province of Pakistan, learning the Sindhi language is mandatory, as it serves as the medium of instruction for most subjects. However, Sindhi is considered one of the more challenging languages to learn, primarily due to its complex grammatical structures and extensive set of characters. This study focuses on enhancing the learning of the Sindhi alphabet among lower-grade students. A survey was conducted in various public and private schools to identify the specific difficulties students face when learning the Sindhi alphabet. The results revealed that most students struggled with three main issues: the number of dots on characters, the placement of dots, and distinguishing between characters with similar pronunciations. Additionally, the study observed that traditional teaching methods were insufficient to engage students and motivate them to learn effectively. To address these challenges, a Game-Based Learning (GBL) approach was implemented by developing a prototype using Android Studio. The prototype incorporated four interactive educational activities designed to improve students’ understanding of the Sindhi alphabet. A comparative performance analysis was conducted between a control group, which used conventional teaching methods, and an experimental group, which engaged with the developed game. The results of the evaluation indicated that the experimental group performed significantly better across all activities compared to the control group, demonstrating the effectiveness of the GBL approach in enhancing the learning experience for students.